Immersion education international perspectives - Johnson, Robert Keith; Swain, Merrill (Cambridge applied linguistics, 1997)
The wide range of languages and purposes now served by immersion worldwide is illustrated by case studies of thirteen programs. Immersion, a relatively new approach to bilingual education, originated in Canada. It uses the target language as a medium of instruction in order to achieve "additive bilingualism" -- a high level of second language proficiency. The wide range of languages and purposes now served by immersion worldwide is illustrated by case studies of thirteen programs presented and discussed in this paperback edition. The introductory chapter defines immersion education theory and practice and shows how this approach differs from other forms of bilingual education